Kontruksi Matematika Berdasarkan Teori Apos - Rizki Rahmadhani; Ariantje Dimpudus (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research explains mathematical constructions using APOS theory which are used to improve students' understanding abilities in the learning process. The method used in this research is literature study. The conclusion in this research is that mathematical construction based on apos theory can improve students' understanding abilities, apart from increasing students' understanding abilities it can also make students more active in learning. Research conclusions This is proven by various research results from other people that have been carried out previously